Potential of Preoperative Testosterone Stimulation Therapy to Reduce Complication in Hypospadias Repair: A Systematic Review and Meta-Analysis - Munawwir, Abdul; Mustamar, Fikri Akbar; Palinrungi, Muhammad Asykar; Aristo, Aristo (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2025)
Introduction. The pre-operative hormone stimulation is recommended for hypospadias patients, especially those with small penis, to improve the results and outcomes of hypospadias repair. We conducted a systematic review and meta-analysis to evaluate the effectiveness of pre-operative testosterone stimulations before hypospadias repair. Methods. We performed a comprehensive search for relevant studies from PubMed, Medline, Cochrane, Proquest, and Embase from August 2000 until August 2023 . The phrases